ANALISIS PENGARUH PERSEPSI TEKNOLOGI, PERSEPSI RESIKO TERHADAP KEPERCAYAAN DAN DAMPAKNYA TERHADAP KEPUASAN BELANJA ONLINE MAHASISWA DI PEKANBARU - Awliya Afwa '; Samsir ' '; Sulistyowati ' ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
Analyze the influence of Perceived Technology, Perceived Risk Against Trust and Its Impact on Student Satisfaction in Online Shopping Pekanbaru under the guidance of Dr. Samsir, SE, M.Si and Dra. Hj. Lilis Sulistyowati, MM. The purpose of this study was to determine the effect of technology perception and the perception of risk in online trust and how trust-related online shopping satisfaction. This study also examines the impact of online trust in mediating the relationship between technology and the perceived satisfaction of online shopping. The population in this study were students enrolled in universities and colleges in the city of Pekanbaru. The samples of 176 people by using purposive sampling method with the criteria of students who have ever shopped online and sampling is done through snowball sampling method in order to make it easier to get the respondent. Data processing is done using path analysis with SEM Smart PLS. The results of this study indicate descriptively respondents are predominantly student at the University of Riau precisely the economic faculty of products purchased online by students is a fashion product. Directly influence the perception of technology that can negatively affect the perception of risk, and perception of technology positively influence the trust and satisfaction of online shopping, then the risk perception negatively affect the trust and satisfaction of online shopping. For the indirect effect is that the perception of risk perception and technology influence the online shopping satisfaction is mediated by the trust.Kata Kunci : Online Shopping, Perceived Technology, Perceived Risk, Trust, Customer Satisfaction.